Kajian Kajian Subtitusi Pati Garut (Maranta arundinacea) Alami Dan Termodifikasi Pada Karakteristik Roti Manis Dengan Penambahan Tepung Kacang Merah - Aldi Riyansah; Desiana Nuriza Putri; Damat Damat (Universitas Muhammadiyah Malang, 2019)
The current pattern of public consumption leads to practical food products in the presentation, such as noodles, bread, and other snacks. This consumption pattern has resulted in increased demand for starch-based foodstuffs. The use of wheat flour that makes Indonesia continues to increase the percentage of imported food every year. The use of natural and modified starch is functioning as a substitute for wheat flour. The starch has a resistant starch. Resistant starch is a starch that can not be digested by digestive enzymes and resistant to stomach acid so it can reach the large intestine to be fermented by probiotic bacteria. This study aims to determine the effect of substitution of natural and modified starch by adding red bean flour to the physical-chemical characteristics of sweet bread. The research was conducted by using Rancangan Acak Kelompok (RAK) two factors. The factor I is the composition of wheat flour and garut starch with 6 levels of natural garut starch 90%: 10%, 80%: 20%, 70%: 30% and modified starch 90%: 10%, 80%: 20%, 70%: 30%. Factor II is the added red kidney bean flour with 2 levels is 5% and 10%. The parameters of this research are texture, pore uniformity, proximate analysis, and organoleptic test.